Speciation of sophisticated toxic elements - Rahman, Md. Mokhlesur; Mohd Noor, Alias; Wood, Khalik (Adi Mullick Brothers, 2017)
In the scientific discussion of chemical cycling and toxicity, it is recognized that particular behaviours of trace metals are determined by their specific forms rather than by their total concentration. Such experience led to the introduction of the term "speciation,” which is used in a vague manner both for the operational procedure for determining typical metal species in environmental samples and for describing the distribution and transformation of such species in various media. Speciation of a certain element in the latter means characterizing its solubility, reactivity and bioavailability in different environmental compartments. It is at first affected by its source, e.g. from natural weathering, industrial processing, use of metal components, leaching from garbage and solid waste dumps, animal and human excretions. In the course of its terrestrial and aquatic cycling, varying physico-chemical conditions may significantly change the distribution of the element species and its behavior in the biogeochemical processes. Characterizing the mobility of a certain element species at a molecular, organelle and cellular level, with respect to its "bioavailability" and "toxicity,” requires further insights into the interactions of different metals with complexing ligands of its physiological concentration . I was the lead investigator, responsible for all major areas of concept formation, data collection and analysis, as well as manuscript composition. Professor Alias Mohd Yusof was involved in the early stages of concept formation and contributed to the editing of the manuscript. Professor Alias Mohd Yusof was the supervisory author on this project and was involved throughout the project in concept formation and manuscript composition. A version of Chapter 2 to Chapter 4 has been published in the following Journals: “The Malaysian Journal of Analytical Sciences,” Vol. 16 (2) (2012): 194 - 201, “Advanced Materials Research” Vol. 264-265 (2011), 1684-1689, and “Nuclear Science Journal of Malaysia,” 18(2), (2000), 19-29, respectively [M. M. Rahman et al.]. I was the lead investigator, responsible for all major areas of concept formation, data collection and analysis, as well as the majority of the manuscript composition. Professor Alias Mohd Yusof and Professor Dr. Khalik Wood were involved in the early stages of the concept formation and contributed to the entire research works. Both of them were the supervisory authors on this project and were involved throughout the project in concept formation, publishing and editing the manuscript. I was also the lead investigator for the projects located in Chapters 3 and 4 where I was responsible for all major areas of concept formation, data collection and analysis, as well as the majority of the manuscript composition. Professor Dr. Khalik Wood were involved in the early stages of the concept formation and contributed to the quality data produced. Dr. Suhami Hamza and Miss Shamsia contributed to the data collection as well as the editing of the articles.